The Life Story Board as a Tool for Qualitative Research: Interviews With HIV-Positive Indigenous Males. Issue 1 (20th January 2018) - Chongo, Meck; Chase, Robert M.; Lavoie, Josée G.; Harder, H. G.; Mignone, Javier
Within the context of a study about the lived experiences of Indigenous males living with HIV in Vancouver, Canada, we explored the utilization of an innovative method of collecting the narratives of study participants. This article describes and assesses the use of the Life Story Board (LSB) as a potentially rich interview tool for qualitative research and explores the process, as well as its advantages and challenges. The LSB uses sets of cards, markers, and notation on a play board to create a visual representation of a verbal narration about someone's life situation or story. Five study participants took part in a conventional face-to-face interview and 4 months later were interviewed with the use of the LSB. These study participants were asked toward the end of the LSB session about their experience of being interviewed with and without the LSB. Data were also gathered from the interviewers' experience. The findings suggested that the LSB offers interesting opportunities when used in qualitative research. Study participants found it to facilitate a reflective and more in-depth narration of their lived experience. The interviewer's perspective for the most part corroborated these observations.